The Effects Of Mitragynine From Mitragyna Speciosa On The Mrna Expression Of Cox-1 And Cox-2 In Lipopolysaccharide-Stimulated Raw264.7 Macrophage Cells - Utar, Zulkhurnain (2014)
Mitragyna speciosa Korth (Rubiaceae) is one of the medicinal plants used traditionally to treat various types of diseases especially in Thailand and Malaysia. Its anti-inflammatory and analgesic properties of its crude form are well documented. In this study, the cellular mechanism involved in the anti-inflammatory effects of mitragynine, the major bioactive constituent, was investigated. The effects of mitragynine on the mRNA and protein expression of COX-1 and COX-2 and the production of prostaglandin E2 (PGE2) were investigated in LPS-treated RAW264.7 macrophage cells. Quantitative RT-PCR was used to assess the mRNA expression of COX-1 and COX-2. Protein expression of COX-1 and COX-2 were assessed using Western blot analysis and the level of PGE2 production was quantified using Parameter™ PGE2 Assay (R&D Systems).